Chronic Gastritis in Dermatitis Herpetiformis: A Controlled Study - Anna Alakoski; Teea T. Salmi; Kaisa Hervonen; Hannu Kautiainen; Maarit Salo; Katri Kaukinen; Timo Reunala; Pekka Collin (Clinical and Developmental Immunology)
Background and Objective. Previous small studies suggest that chronic atrophic gastritis is common in dermatitis herpetiformis (DH). We here examined the frequency and topography of chronic gastritis in 93 untreated DH subjects and in 186 controls with dyspepsia. Methods. Specimens were drawn from the gastric corpus and antrum and examined for atrophy, intestinal metaplasia, and Helicobacter pylori. Duodenal biopsies were taken. Results. Atrophic corpus gastritis was more frequent in DH than in controls (16.0% and 2.7%, resp., P<0.001); atrophy in the antrum was rare in both groups (3.2% and 1.1%, P=0.34). Intestinal metaplasia was present in 13 (14.0%) DH and 12 (6.5%) control patients (P=0.038) and H. pylori in 17 (18.3%) and 17 (9.3%) (P=0.028), respectively. Small-bowel villous atrophy was seen in 76% of the DH patients, equally in patients with and without chronic gastritis. One DH patient with atrophic gastritis developed gastric cancer. Conclusion. In DH, chronic atrophic gastritis was common in the corpus, but not in the antrum. H. pylori will partly explain this, but corpus atrophy is suggestive of an autoimmune etiology. Atrophic gastritis may increase the risk of gastric cancer. We advocate performing upper endoscopy with sufficient histologic samples in DH.